Economic Models of Higher Education: An International Perspective - Ruffini, Pierre-Bruno (International Dialogues on Education Journal, 2015)
As other sectors, higher education can be characterized by the combination of market mechanisms and state intervention in its funding and organization. Although higher education systems of developed countries pursue similar goals (provide high-level manpower, meet individual and social demands, etc.) and face similar challenges (massive expansion, internationalization, MOOCs, etc.) their economic models differ significantly. In some countries, universities are public and charge no or very low tuition fees, whereas in other countries, the cost-sharing with parents and students is much more demanding. The paper will try to underscore and explain these differences by drawing on the lessons of economic analysis and on the historical and cultural background of countries.